Budowa i funkcjonowanie bydgoskich osiedli mieszkaniowych Kapuściska i Łęgnowo w latach 1945-1956 (Kronika Bydgoska, 2013)
In the years of the so-called Polish Stalinism, the authorities started the construction of big heavy industry centres. The assumption was to construct workers’ complexes provided with everything necessary to live around industrial plants. Thus, housing estates, hospitals, schools, shops, kiosks, culture centres, sports facilities, libraries, health care centres, as well as restaurants and beer houses were constructed on the limits of industrial giants. This was motivated by safety reasons and thorough surveillance of the citizens. Housing estates constructed with a huge propaganda blast, in the socialist realism style typical at that time. It was similar as regards the housing estates Kapuściska and Łęgnowo. To this day, Kapuściska has been a housing estate being the largest trace of the Polish Stalinism epoch in Bydgoszcz. These housing estates were constructed out of the will to provide the workers of the Chemical Plant ”Zachem” with flats. The constructed blocks of flats were to be self-sufficient and form closed enclaves of residents subject to control due to the military production, especially explosives.